2016
DOI: 10.1021/acs.analchem.6b00999
|View full text |Cite
|
Sign up to set email alerts
|

Aptazyme–Gold Nanoparticle Sensor for Amplified Molecular Probing in Living Cells

Abstract: To date, a few of DNAzyme-based sensors have been successfully developed in living cells; however, the intracellular aptazyme sensor has remained underdeveloped. Here, the first aptazyme sensor for amplified molecular probing in living cells is developed. A gold nanoparticle (AuNP) is modified with substrate strands hybridized to aptazyme strands. Only the target molecule can activate the aptazyme and then cleave and release the fluorophore-labeled substrate strands from the AuNP, resulting in fluorescence enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
82
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 44 publications
0
82
0
2
Order By: Relevance
“…23,24 And it showed broad prospects for in situ detection of intracellular analytes because no additional tool enzyme is required. [25][26][27] Recently, a TAMRA-tagged substrate strands hybridized to DNAzyme strands functionalized gold nanoparticle probe was designed for in situ uorescence imaging and detection of cytoplasmic ATP activity. 25 Only the target molecule can activate the DNAzyme and then cleave and release the uorophore-labeled substrate strands from the AuNP, resulting in uorescence enhancement.…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 And it showed broad prospects for in situ detection of intracellular analytes because no additional tool enzyme is required. [25][26][27] Recently, a TAMRA-tagged substrate strands hybridized to DNAzyme strands functionalized gold nanoparticle probe was designed for in situ uorescence imaging and detection of cytoplasmic ATP activity. 25 Only the target molecule can activate the DNAzyme and then cleave and release the uorophore-labeled substrate strands from the AuNP, resulting in uorescence enhancement.…”
Section: 6mentioning
confidence: 99%
“…[25][26][27] Recently, a TAMRA-tagged substrate strands hybridized to DNAzyme strands functionalized gold nanoparticle probe was designed for in situ uorescence imaging and detection of cytoplasmic ATP activity. 25 Only the target molecule can activate the DNAzyme and then cleave and release the uorophore-labeled substrate strands from the AuNP, resulting in uorescence enhancement. However, the above-mentioned method has the disadvantages of lacking simplicity, suffering from time-consuming processes caused by immobilization of DNAzyme on gold nanoparticles, relatively poor salt stability of gold nanoparticles as signal transducer, which present some limitations for their practical implementation.…”
Section: 6mentioning
confidence: 99%
“…The Wang group has developed several DNAzyme functionalized gold nanoparticle‐based probes for live cell imaging. For example, Yang et al reported the first aptazyme‐based gold nanoparticle probe for the detection of ATP in live cells ( Figure ) . A 13‐nm gold nanoparticle was densely functionalized with 3′‐TAMRA‐labeled substrate strands to which 5′‐BHQ‐2‐labeled aptazymes specific for ATP were hybridized.…”
Section: Dnazyme‐based Probesmentioning
confidence: 99%
“…Active aptazymes can bind to multiple substrate strands in succession, leading to amplified signal. Adapted with permission . Copyright 2016, American Chemical Society.…”
Section: Dnazyme‐based Probesmentioning
confidence: 99%
“…C rystalline nanomaterials can be conjugated with a variety of biomolecules, including peptides, proteins (e.g., antibodies and enzymes), nucleic acids (e.g., aptamers), and lipids, for enhancing their biocompatibility and in vivo circulation, as well as for enabling cell recognition and intracellular delivery [1][2][3][4][5] . This approach is becoming increasingly prominent for diagnosis and treatment of cancer, anemia, diabetes, and Alzheimer's disease via nano-enabled biosensors, bioimaging, and drug delivery [6][7][8] . Significant attention has focused on modulating the interaction between crystalline nanomaterials and biomolecules through manipulating the morphology, particle size, and surface functionalities of nanocrystals [9][10][11][12] , whereas exposed crystal facets, one of the most intrinsic properties of crystalline nanomaterials, remain largely unexplored.…”
mentioning
confidence: 99%